Pharmacokinetics of Curcumin Conjugate Metabolites in Healthy Human Subjects - Vareed, Shaiju K. (2008)
BACKGROUND: Curcumin is a polyphenol, found in the spice turmeric, that has promising anticancer properties, but previous studies suggest that absorption of curcumin may be limited. METHODS: This study examined the pharmacokinetics of a curcumin preparation in healthy human volunteers 0.25-72 hours after a single oral dose. Curcumin was administered at doses of 10 g (N=6) and 12 g (N=6). Subjects were randomly allocated to dose level for a total of 6 subjects at each dose level. Serum samples were assayed for free curcumin, for its glucuronide and for it sulfate conjugate. The data were fit to a one-compartment absorption and elimination model. RESULTS: Using an HPLC assay with a limit of detection of 50 ng/mL, only one subject had detectable free curcumin at any of the 14 time points assayed, but curcumin glucuronides and sulfates were detected in all subjects. Based on the PK model, AUC for the 10g and 12 g doses was estimated (mean±standard error) to be 35.33±3.78 and 26.57±2.97 μg/mL × hr, respectively, while C(max) was 2.30±0.26 and 1.73±0.19 μg/mL. The t(max) and t(1/2) were estimated to be 3.29±0.43 hr and 6.77±0.83 hr. The ratio of glucuronide:sulfate was 1.92:1. The curcumin conjugates were present as either glucuronide or sulfate, not mixed conjugates. CONCLUSION: Curcumin is absorbed after oral dosing in humans and can be detected as glucuronide and sulfate conjugates in plasma.